RELATIONSHIP LEVEL OF EDUCATION AND COMMUNITY ECONOMY WITH LAW OWNERSHIP IN BAHARU VILLAGE, SUSOH DISTRICT, DISTRICT SOUTHWEST ACEH IN 2021 - zubir (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2022)
Background: Many environmental health facilities have been built by agencies, both government, private, and NGOs (non-governmental organizations). Many projects for the provision of environmental sanitation facilities have been built for the community, for example: family latrines, public latrines, garbage bins and so on. However, due to community behavior, these sanitation facilities or facilities are not properly utilized and maintained. In order for the environmental sanitation facilities to be used and maintained optimally, it is necessary to provide health education for the community. Research Objectives To find out the relationship between the level of education and the economy of the community and ownership of latrines in Baharu Village, Susoh District, Aceh Barat Daya District in 2013. This research method is descriptive with a cross-sectional design, namely a study that aims to determine the relationship between the level of education and the economy of the community and latrines ownership. in Baharu Village, Susoh District, Southwest Aceh District in 2013. The number of samples in this study were heads of families in Baharu Village, Susoh District, Southwest Aceh District in 2013, totaling 72 families (total population). Data was collected using observation and interview methods. Data analysis uses Univariate analysis, namely the analysis carried out on each variable from the research results. The results of research on 72 families in Baharu Village, Susoh District, Southwest Aceh District, which was carried out for 3 days on June 9 and 10 and 11, obtained the following results: